The Potential of Activated Carbon Production from Leucaena leucocephala charcoal and Application in Melanoidin Removal - Insoongnoen, Bang-orn; Yimrattanabovorn, Jareeya; Wichitsathian, Boonchai (Naresuan University Journal: Science and Technology (NUJST), 2020)
Melanoidins are brown recalcitrant compounds present in the effluents of ethanol production, and brewery industry. It is difficult to biodegrade by the conventional treatment processes. Adsorption process was reported to have achieved more than 90% of melanoidin removal. However, due to its high operating cost has limited its use for wastewater treatment, alternative low-cost adsorbents are finding from various materials such as plant waste. The L. leucocephala was reported as a potential material for adsorbent due to their properties. The aim of this work was to produce the low-cost adsorbent L. leucocephala activated carbon (LAC) derive from L. leucocephala char by CO 2 activation method. Batch experiments were carried out to determine the optimum conditions for melanoidin adsorbed on LAC samples. Kinetic data and adsorption equilibrium isotherm were done in the batch experiments. The results showed the LAC samples had the high surface areas in the range of 823.63-1,596.20 m 2 /g. Maximum adsorption capacity of melanoidin on the LAC samples were found in the range of 588.24-1,666.67 mg/g. The optimum adsorption conditions of the LAC were obtained at the contact time of 480 min, the initial melanoidin concentration of 1,000 mg/L, the initial solution pH of 2, the agitation speed of 100 rpm and the temperature of 65˚C. This finding is a useful tool for scale-up and design purposes to apply for wastewater treatment of industry. It can be concluded that the LAC is a potential material to produce as a low-cost adsorbent for the removal of melanoidin from wastewater.   Keywords: Melanoidin, Adsorption, Leucocephala , Activated carbon, Low-cost adsorbent